A digital protein microarray for COVID-19 cytokine storm monitoring. Issue 2 (19th November 2020) - Song, Yujing; Ye, Yuxuan; Su, Shiuan-Haur; Stephens, Andrew; Cai, Tao; Chung, Meng-Ting; Han, Meilan K.; Newstead, Michael W.; Yessayan, Lenar; Frame, David; Humes, H. David; Singer, Benjamin H.; et al.
Abstract : A digital microfluidic immunoassay platform enables rapid multiplex quantification of proinflammatory cytokines in serum for critically ill COVID-19 patients. Abstract : Despite widespread concern regarding cytokine storms leading to severe morbidity in COVID-19, rapid cytokine assays are not routinely available for monitoring critically ill patients. We report the clinical application of a digital protein microarray platform for rapid multiplex quantification of cytokines from critically ill COVID-19 patients admitted to the intensive care unit (ICU) at the University of Michigan Hospital. The platform comprises two low-cost modules: (i) a semi-automated fluidic dispensing/mixing module that can be operated inside a biosafety cabinet to minimize the exposure of the technician to the virus infection and (ii) a 12–12–15 inch compact fluorescence optical scanner for the potential near-bedside readout. The platform enabled daily cytokine analysis in clinical practice with high sensitivity (<0.4 pg mL −1 ), inter-assay repeatability (∼10% CV), and rapid operation providing feedback on the progress of therapy within 4 hours. This test allowed us to perform serial monitoring of two critically ill patients with respiratory failure and to support immunomodulatory therapy using the selective cytopheretic device (SCD). We also observed clear interleukin-6 (IL-6) elevations after receiving tocilizumab (IL-6 inhibitor) while significant cytokine profile variability exists across all critically ill COVID-19 patients and to discover a weak correlation between IL-6 to clinical biomarkers, such as ferritin and C-reactive protein (CRP). Our data revealed large subject-to-subject variability in patients' response to COVID-19, reaffirming the need for a personalized strategy guided by rapid cytokine assays.